P203 Effects of ethnicity and socioeconomic status on surgical outcomes from inflammatory bowel disease. (19th June 2022) - Stamatiou, Dimitrios; Naumann, David; Foss, Helen; Singhal, Rishi; Karandikar, Sharad
Abstract : Introduction: Evidence suggests that ethnicity and socioeconomic status of patients with chronic diseases influence their healthcare outcomes. The aim of this study was to assess the impact of these factors on the surgical outcome of patients with inflammatory bowel disease (IBD) over a 15-year period. Methods: A retrospective observational study investigated IBD patients operated on at an NHS Trust between 2000-2015, with follow up data until 2020. Logistic regression models were used to determine the relationship between ethnic minority background and Index of Multiple Deprivation (IMD) on outcomes including requirement for intra-abdominal surgery, permanent stoma, re-do surgery and surgical complications, accounting for age, gender, smoking history and biologic treatment. Results: There were 1, 620 patients (56.7% Ulcerative Colitis (UC) and 43.3% Crohn's Disease (CD)). Median age was 32 years and 49.6% were female. Patients with an ethnic minority background accounted for 20.6%. Within 5-years of first presentation, 369 patients required intra-abdominal surgery, 95 permanent stomas and 107 re-do surgery. For CD patients, younger age at diagnosis, female patients, those with an ethnic minority background, higher IMD quintile, smoking history and biologic treatment were more likely to have intra- abdominal surgery. Ethnic minority background and higher IMD score were further associated with surgical complications for CD but not UC patients. Conclusions: Ethnic minority status and socioeconomic deprivation were associated with worse surgical outcomes within our cohort of IBD patients. These findings may stimulate discourse regarding the strategic planning of equitable healthcare services.